Original Article - Cerebral Vein Thrombosis in St. James’s Hospital- Incidence, Predisposing Factors and Sequelae - Appleby, Niamh (Trinity Student Medical Journal, 2006)
Background: Thrombosis of the cerebral veins and sinuses is a cerebrovascular disorder most commonly affecting young adults. Underlyingrisk factors for cerebral vein thrombosis (CVT) are identified in 85% of patients. This study aims to identify the underlying risk factors in a cohort of patients with a diagnosis of CVT and identify of recurrent events. Methods: A retrospective analysis of data from a cohort of 12 patients with a diagnosis of cerebral vein or sinus thrombosis was performed. Results: 12 patients (10 female, 2 male, median age 30.5 years) with cerebral vein or sinus thrombosis were identified. Ten patients (83%) had a known risk factor for CVT. Thrombophilia (genetic or acquired), use of oral contraceptives, pregnancy and post-partum and infection were the most commonly identified risk factors. Two patients (17%) experienced a recurrence of CVT. Conclusion: The mode of presentation of CVT and its risk factors identified here are similar to those described in international studies. No woman with intrapartum CVT has experienced a recurrence thrombosis to date. Further data is required to provide evidence based management guidelines for the subgroup of women who present with CVT during pregnancy and for the group of women with a history of CVT who become pregnant subsequently.